An Analysis on the Use of Cohesion and Coherence in Students’ Writing - Rizky Takriyanti; Fransisko Chaniago; Hamdan Hamdan (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2021)
This study is aimed at knowing the types of cohesion and coherence uses in writing a descriptive text by English Education Program students. The researcher focused on lexical cohesion, repeated key nouns, and consistent pronouns. The method used in this study is a qualitative. The data were collected by using a test and documentation. Participants of the research were twenty two students. The finding showed that nine students used fifteen items of reiteration and one student used collocation. In coherence, the researcher found that all students used repeated key nouns in their writing with 131 items used. Then, fifteen students used sixteenitems of consistent pronouns. From the research, it can be concluded that the students used cohesion and coherence well in their writing.